Can Audit Fees and Auditor Competence Affect Auditor Motivation? - Susanto, Edy (Advances in Managerial Auditing Research, 2023)
The purpose of this study was to determine and analyze the effect of audit fees and auditor competence on auditor motivation at the Public Accounting Firm (KAP) in Makassar city. The population in this study were all auditors who worked at KAP in Makassar, totaling 48 auditors. The sample selection was carried out using the census method, in which all members of the population were used as samples. The data used in this study are primary data collected by distributing questionnaires to all respondents, with data analysis techniques that will be carried out namely descriptive statistical tests, validity and reliability tests, classical assumption tests, multiple linear regression analysis and hypothesis testing which consists of testing partial (t test) and simultaneous test (f test). The results of the study show that audit fees have a positive and significant effect on auditor motivation. This indicates that the greater the fee received by an auditor, the more motivated he is in carrying out his duties. Meanwhile, auditor competence has a negative and significant effect on auditor motivation at the Public Accounting Firm in Makassar city